“From where to where?” Exploring the notion of place in children’s picture books and graphic novels about refugees - Kouraki, Chryssa; Vorylla , Varvara (ΚΕΙΜΕΝΑ για την έρευνα, τη θεωρία, την κριτική και τη διδακτική της Παιδικής και Εφηβικής Λογοτεχνίας, 2022)
This paper will attempt to bring out approaches to the issue of the refugees in a sample of Anglophone literary production of 2016, the year following the great refugee crisis, focusing on children’s picture books. In particular, the aspect of “place” was selected to explore its importance and function since it is a notion at the heart of the refugee transition process. “Place” is analyzed as the refugees’ sending and receiving a place in both the books’ narration and illustration. In addition, it is attempted to interpret the interrelation between “place” and characters and the possible symbolic dimension that place can have in words and images. This paper attempts to explore how the issue of refugees is depicted in a sample of children’s picture books and graphic novels of Anglophone literary production of 2016, the year following the 2015 refugee crisis. In particular, it is the aspect of “place” that was selected to explore because of its importance and function since it is a notion at the heart of the refugee transition process. “Place” is viewed in terms of narration and illustration as the two ends of a transition: the starting point-homeland and the destination of a long fleeing journey. In addition, an interpretation of the interrelation between “place” and characters is attempted along with the analysis of the symbolic dimension that “place” can have given by words and images. Αυτή η εργασία επιχειρεί να διερευνήσει πώς απεικονίζεται το ζήτημα των προσφύγων σε ένα δείγμα παιδικών εικονογραφημένων βιβλίων και graphic novels της αγγλόφωνης λογοτεχνικής παραγωγής του 2016, το έτος μετά την προσφυγική κρίση του 2015. Ειδικότερα, το θέμα που επιλέχθηκε να αναλυθεί είναι ο τόπος, λόγω της σημασίας και της λειτουργίας του στη διαδικασία μετάβασης των προσφύγων. Ο «τόπος» αντιμετωπίζεται από την άποψη της αφήγησης και της εικονογράφησης ως τα δύο άκρα μιας μετάβασης: η αφετηρία-πατρίδα και ο προορισμός ενός μακρινού ταξιδιού φυγής και σωτηρίας. Επιπρόσθετα, επιχειρείται η ερμηνεία της αλληλεπίδρασης μεταξύ του «τόπου» και των χαρακτήρων, καθώς και της συμβολικής διάστασής του μέσα από τις λέξεις και τις εικόνες.